2019
DOI: 10.3171/2018.8.spine18586
|View full text |Cite
|
Sign up to set email alerts
|

Updated imaging does not affect revision rates in adults undergoing spine surgery for lumbar degenerative disease

Abstract: OBJECTIVEDiagnostic workup for lumbar degenerative disc disease (DDD) includes imaging such as radiography, MRI, and/or CT myelography. If a patient has unsuccessful nonoperative treatment, the surgeon must then decide if obtaining updated images prior to surgery is warranted. The purpose of this study was to investigate whether the timing of preoperative neuroimaging altered clinical outcome, as reflected by the subsequent rate of revision surgery, in patients with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Patients reviewed during the survey had a mean age of 56.5 6 11.7 years and an average body mass index of 28.8 6 5.35 kg/m 2 . Of the 30-patient cohort, 56.7% (17) were women. The two most common patient co-morbidities were hypertension (34.6%, n = 9) and sleep apnea (15.4%, n = 4), and a tie for third most common comorbidity was observed between diabetes mellitus (7.7%, n = 2), coronary artery disease (7.7%, n = 2), and atrial fibrillation (7.7%, n = 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients reviewed during the survey had a mean age of 56.5 6 11.7 years and an average body mass index of 28.8 6 5.35 kg/m 2 . Of the 30-patient cohort, 56.7% (17) were women. The two most common patient co-morbidities were hypertension (34.6%, n = 9) and sleep apnea (15.4%, n = 4), and a tie for third most common comorbidity was observed between diabetes mellitus (7.7%, n = 2), coronary artery disease (7.7%, n = 2), and atrial fibrillation (7.7%, n = 2).…”
Section: Resultsmentioning
confidence: 99%
“…Although the FLSR is a single element in the broad presurgical picture, it is, nonetheless, a necessary component of evaluation. 1 Although still somewhat controversial, 17 the use of preoperative FLSR in patients with lumbar degenerative spinal stenosis is associated with fewer subsequent revision procedures, when compared with MRI or CT myelogram. 16 When considering this along with our observation that FLSRs can reduce the variation of surgical plans, this study demonstrated the need to investigate further the ability of FLSRs to decrease costs and to reduce patient morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that occult bacteria can be “ present in tissues deep below the skin before surgery ” in patients undergoing primary spine surgeries 9 . Revision spine surgery, which has a 5-year incidence of 10% to 18% 22 in degenerative lumbar spinal disorder and 6% to 20% 23 in adult spinal deformity, has also been found to often carry subclinical infections 24 . In a retrospective review of 595 revision spine surgeries performed for indications other than infection, operative cultures were obtained in 19% (112) of the cases, 40% (45) of whom tested positive 24 .…”
Section: Discussionmentioning
confidence: 99%